The Collection of Adipose Derived Stem Cells using Water–Jet Assisted Lipoplasty for their Use in Plastic and Reconstructive Surgery: A Preliminary Study - Purpura, Valeria; Bondioli, Elena; Melandri, Davide; Parodi, Pier C.; Valenti, Luca; Riccio, Michele (Frontiers in Cell and Developmental Biology, 2016)
The graft of autologous fat for the augmentation of soft tissue is a common practice frequently used in the field of plastic and reconstructive surgery. In addition, the presence of adipose derived stem cells (ASCs) in adipose tissue stimulates the regeneration of tissue in which it is applied after the autologous fat grafting improving the final clinical results. Due to these characteristics, there is an increasing interest in the use of ASCs for the treatment of several clinical conditions. As a consequence, the use of clean room environment is required for the production of cell-based therapies. The present study is aimed to describe the biological properties of adipose tissue and cells derived from it cultured in vitro in clean room environment according to current regulation. The collection of adipose tissue was performed using the water – jet assisted liposuction in order to preserve an high cell viability increasing their chances of future use for different clinical application in the field of plastic and reconstructive surgery.